Fabrication and Characterization of Cytochrome C Modified Poly(3-Aminobenzoic Acid) Thin Film - Saengrawee Sriwichai (2018)
Copyright © Taylor & Francis Group, LLC. The electropolymerized poly(3-aminobenzoic acid) (PABA) film on indium tin oxide electrode was used for fabrication of cytochrome c (Cyt c) modified PABA thin film upon immobilization of Cyt c onto the PABA surface. The obtained Cyt c modified PABA thin film was characterized by UV-vis spectroscopy, XPS, AFM, and SEM-EDX techniques. Shifts of the UV-vis absorption peaks were observed from Cyt c modified PABA thin film compared with Cyt c solution and PABA thin film. The formation of the covalent amide bond between the carboxylic groups of PABA and amine groups in Cyt c was observed from XPS results. © 2015